Integrated Control of Economic Security by Machine Learning in the Information Space of the Digital Economy - Voronin, E. A.; Kozlov, S. V.; Kubankov, A. N. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The paper considers a refined statement of the economic security control problem in the formation of a digital economy, developed on the basis of a probabilistic assessment of the implementation of organizational, technical and technological processes for ensuring economic security using a universal methodology. Methods and technologies for applying machine learning in control and ensuring of economic security, based on data from the information space of the digital economy, are given. A methodology and methods for assessing and predicting threats, assessing the vulnerability of economic systems and choosing the optimal strategy to counter them are proposed. Algorithms and the most suitable programming languages for the implementation of solutions to the problem are selected. It is possible only if there is an information space organized according to the paradigm of the digital economy.